2015
DOI: 10.1002/biof.1206
|View full text |Cite
|
Sign up to set email alerts
|

Punica granatum and its therapeutic implications on breast carcinogenesis: A review

Abstract: Punica granatum has a recorded history of pharmacological properties which can be attributed to its rich reservoir of phytochemicals. Investigations in recent years have established its tremendous potential as an antitumorogenic agent against various cancers including breast cancer, which is the second leading cause of cancer-related deaths in women. The plausible role of Punica as a therapeutic agent, as an adjuvant in chemotherapy, and its dietary implications as chemopreventive agent in breast cancer have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 72 publications
(102 reference statements)
1
19
0
1
Order By: Relevance
“…Additionally, our earlier studies have shown that PME, as such in ovariectomized mice, can bring down levels of LDL, TC and TG similar to the observed action of 17‐β‐estradiol while maintaining the HDL levels .…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, our earlier studies have shown that PME, as such in ovariectomized mice, can bring down levels of LDL, TC and TG similar to the observed action of 17‐β‐estradiol while maintaining the HDL levels .…”
Section: Discussionsupporting
confidence: 62%
“…Limer and Speirs reported that high consumption of phytoestrogens, which are very weak mimics of natural oestrogens, is associated with a lower incidence of breast cancer. Pomegranate (PME) fruit is such an entity, and several studies have been conducted to evaluate the efficacy of this fruit endowed with a very high antioxidant activity antiproliferative, anti‐invasive, antiaromatase and proapoptotic agents in various breast cancer cell lines and animal models . We have earlier demonstrated that the methanolic extract of PME can act as a SERM in breast cancer cell lines and ovariectomized mice and had a strong lipid‐lowering action, that is, it decreased the plasma levels of total cholesterol (TC) and triglyceride (TG) in ovariectomized animals and was comparable to tamoxifen and estradiol.…”
Section: Introductionmentioning
confidence: 99%
“…Punica granatum has been considered to be pharmacologically active due to the presence of abundant phytochemicals [29,30]. The different parts of the plant consist of various chemical compounds that impart crucial roles in the prevention of many diseases [25].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Das ist insbesondere deshalb interessant, da der Androgenrezeptor im hormonrefraktären Stadium häufig überexprimiert ist [57]. Granatapfel-Polyphenole verringern zudem die Bildung von Androgensynthese-E n z y m e n i n h o r m o n r e f r a k t ä r e n K r e b s z e l l e n [ 3 liche Stufen der Krebsentstehung Einfluss nimmt (Proliferation, Invasion, Migration, Metastasen, Angiogenese, Entzündungen) [83].…”
Section: Hormonrefraktärer Prostatakrebsunclassified